Identifikasi Aliran Sampah di Kota Semarang Melalui Pengelolaan Sampah Berbasis Masyarakat - Ramadan, Bimastyaji Surya; Fauziyah, Fita; Budihardjo, Mochamad Arief; Syafrudin, Syafrudin (Universitas Diponegoro, 2019)
Community-based waste management is a form of waste management recommended by the government because it is very effective in creating a zero-waste society. In Indonesia, community-based waste management can be realized through the development of waste banks at the neighbourhoodlevels. In 2019, the City of Semarang has 48 units of active waste banks. Waste that is managed by the wastebank is plastic, paper and metal. However, there is organic waste which is also managed by several wastebanks. The purpose of this study is to identify and analyze the flow of waste through community-basedwaste management, in this case of the waste bank, in the city of Semarang. The method used is in-depth surveys and interviews related to the waste bank management system in the city of Semarang. The results showed that the activity of the existing garbagebank was able to reduce waste in the city of Semarang by 0.07% of the total garbage generation in the city of Semarang. This research can be used as a reference for developing better community-based waste management strategies, especially in Semarang City